Corporate Reputation and Religious Fatwas: An Examination of Unilever Indonesia’s Public Statements - Shifa Ardiana Rachmawati; Syifa Ardiani Rachmawati; Retno Wulan Pawestri; Otniel Christian Putra Delova; Pramudya Ibnu Subrata (Jurnal Genesis Indonesia, 2026)
The reputational crisis facing multinational corporations in Indonesia following MUI Fatwa No. 83 of 2023 represents a complex ideological challenge. This research analyzes the significant boycott pressures experienced by PT Unilever Indonesia Tbk, triggered by perceived geopolitical affiliations regarding the Israel-Palestine conflict. Utilizing qualitative content analysis grounded in Image Restoration Theory, this study examines how defensive narratives were constructed in official press releases to sustain brand resilience. The findings indicate that Unilever implemented strategic communication patterns centered on localization, specifically emphasizing local ownership, domestic operations, and halal certification. Furthermore, the company utilized transcendence strategies by highlighting its commitment to humanitarian aid in Gaza through official agencies. Theoretically, crisis communication effectiveness in religious markets depends heavily on aligning corporate narratives with the legitimacy of local religious authorities. This article serves as a practical guide for Public Relations practitioners in navigating sociopolitical crises while maintaining corporate legitimacy.